MOST sub-arcsecond companions of Kepler exoplanet candidate host stars are gravitationally bound - Horch, E.P.; Howell, S.B.; Everett, M.E.; Ciardi, D.R. (Astrophysical Journal, 2014)
Using the known detection limits for high-resolution imaging observations and the statistical properties of true binary and line-of-sight companions, we estimate the binary fraction of Kepler exoplanet host stars. Our speckle imaging programs at the WIYN 3.5 m and Gemini North 8.1 m telescopes have observed over 600 Kepler objects of interest and detected 49 stellar companions within 1 arcsec. Assuming binary stars follow a log-normal period distribution for an effective temperature range of 3000-10,000 K, then the model predicts that the vast majority of detected sub-arcsecond companions are long period (P > 50 yr), gravitationally bound companions. In comparing the model predictions to the number of real detections in both observational programs, we conclude that the overall binary fraction of host stars is similar to the 40%-50% rate observed for field stars. © 2014. The American Astronomical Society. All rights reserved..
97 citations (Crossref) [2023-10-31]
Keywords: Binaries: visual; Planetary systems; Stars: solar-type; Techniques: high angular resolution; Techniques: interferometric; Techniques: photometric; dept.phy

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Microscopy and team-based interdisciplinary materials research to achieve 21st century skills - Broadbridge, Christine; Sadowski, Thomas; Garofano, Jacquelynn; DaPonte, John S. (Microscopy and Microanalysis, 2014)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00363 tex.type: [object Object]
Keywords: dept.phy

Recent star formation in the leading arm of the Magellanic Stream - Casetti-Dinescu, Dana I.; Bidin, Christian Moni; Girard, Terrence M.; Méndez, Réne A.; Vieira, Katherine; Korchagin, Vladimir I.; Altena, William F. van (The Astrophysical Journal, 2014)
Strongly interacting galaxies undergo a short-lived but dramatic phase of evolution characterized by enhanced star formation, tidal tails, bridges, and other morphological peculiarities. The nearest example of a pair of interacting galaxies is the Magellanic Clouds, whose dynamical interaction produced the gaseous features known as the Magellanic Stream trailing the pair's orbit about the Galaxy, the bridge between the Clouds, and the leading arm (LA), a wide and irregular feature leading the orbit. Young, newly formed stars in the bridge are known to exist, giving witness to the recent interaction between the Clouds. However, the interaction of the Clouds with the Milky Way (MW) is less well understood. In particular, the LA must have a tidal origin; however, no purely gravitational model is able to reproduce its morphology and kinematics. A hydrodynamical interaction with the gaseous hot halo and disk of the Galaxy is plausible as suggested by some models and supporting neutral hydrogen (H I) observations. Here we show for the first time that young, recently formed stars exist in the LA, indicating that the interaction between the Clouds and our Galaxy is strong enough to trigger star formation in certain regions of the LA—regions in the outskirts of the MW disk (R ∼ 18 kpc), far away from the Clouds and the bridge.
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/084-595-728-951-339, pop00078 tex.type: [object Object]
Keywords: Galaxy: general; Magellanic Clouds; dept.phy; galaxies: interactions; stars: early-type

An analytic algorithm to calculate the inclination, ascending node, and semimajor axis of spectroscopic binary orbits using a single speckle measurement and the parallax - Docobo, Jose Angel; Campo, P P; Andrade, Manuel; Horch, Elliott P (Astrophysical Bulletin, 2014)
It is well known that in spectroscopic binary orbits, the inclination, the ascending node, and the semimajor axis remain undetermined, therefore the principal objective of this research is to establish an analytic methodology for the calculation of these parameters for spectroscopic binaries, both single-lined (SB1) and double-lined (SB2). In other words, the goal is to determine their “three-dimensional” orbits using a single speckle measurement (ρ, θ, t) and the parallax (π). Moreover, estimates of the individual masses of each system can also be obtained. The proposed algorithm was successfully applied to SB1 systems: YSC 148 (HD 37393) and CHR 225 (HD 34318), and SB2 systems: LSC 1 Aa1,2 (HD 200077) and Mkt 11 Aa, Ab (HD 358). In this late case, previously determined spectroscopic and visual orbits have been used to compare and contrast the results obtained from them with our results. The methodology presented is especially interesting for those cases in which it is only possible to resolve the spectroscopic binary in the zones of maximum angular separation by optical means thereby making it impossible to avail of sufficient observations in order to calculate the visual orbit. © Pleiades Publishing, Ltd. 2014.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-814-675-311-054 tex.type: [object Object]
Keywords: dept.phy; general; high angular resolution—techniques; interferometric—binaries; techniques

The three-dimensional orbit and physical properties of the binary COU 2031 (WDS 04464+4221, HIP 22196, HD 30090) - Docobo, Jose Angel; Griffin, R F; Tamazian, V S; Horch, Elliott P; Campo, P P (Monthly Notices of the Royal Astronomical Society, 2014)
We report a comprehensive study of the binary system COU 2031, based on simultaneous and independent astrometric visual and speckle observations and on radial-velocity measurements. The similarity of the two orbital solutions allows us to obtain not only a consistent 3D orbit and a precise value of the parallax of the system but also to determine the physical properties of the components. © 2014 The Authors.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/132-132-335-733-638 tex.type: [object Object]
Keywords: Binaries: spectroscopic; Binaries: visual; Stars: individual: COU 2031; dept.phy; peer-reviewed

Characterization of carbon nanotube growth via CVD synthesis from a liquid precursor - Jenkins, Carol; Cruz, Melissa; Depalma, Jen; Conroy, Michael; Benardo, Barbara; Horbachuk, Michael; Sadowski, Tom; Broadbridge, Christine; Schwendemann, Todd C (International Journal of High Speed Electronics and Systems, 2014)
As novel theories and uses of carbon nanotubes (CNT) advance, it becomes increasingly important to characterize the methods of production. One such method of CNT production uses a liquid phase precursor (hydrocarbon with nanoparticle catalyst mix) that is injected into a tube furnace with a flowing carrier gas. The CNTs are grown in high purity and are collected on the surface of the quartz tube. The system allows for a number of variables to be tested such as growth temperatures, flow rate of the carrier gas, precursor injection rates and variations of precursor mix however, here only thermal effects are considered. Under thermal conditions ranging from 500 to 850°C, multi-walled carbon nanotubes (MWCNTs) are synthesized and characterized to determine inner and outer diameter as well as tube thickness. © 2014 World Scientific Publishing Company.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-611-840-548-398 tex.type: [object Object]
Keywords: Carbon nanotube growth; Carbon nanotubes; Carbon nanotubes (CNT); Chemical vapor deposition; Chemical vapor deposition (CVD); Chemical vapor depositions (CVD); Liquid precursors; Liquid-phase precursors; Liquids; Nanoparticle catalysts; Outer diameters; Precursor injection; Thermal condition; Transmission electron microscopy; Transmission electron microscopy (TEM); Tubes (components); dept.phy; peer-reviewed

A high density two-dimensional electron gas in an oxide heterostructure on Si (001) - Jin, Eric N; Kornblum, Lior; Kumah, Divine; Zou, Ke; Broadbridge, Christine; Ngai, J H; Ahn, C H; Walker, Fred (APL Materials, 2014)
We present the growth and characterization of layered heterostructures comprised of LaTiO3 and SrTiO3 epitaxially grown on Si (001). Magnetotransport measurements show that the sheet carrier densities of the heterostructures scale with the number of LaTiO3/SrTiO3 interfaces, consistent with the presence of an interfacial 2-dimensional electron gas (2DEG) at each interface. Sheet carrier densities of 8.9 × 1014 cm-2 per interface are observed. Integration of such high density oxide 2DEGs on silicon provides a bridge between the exceptional properties and functionalities of oxide 2DEGs and microelectronic technologies. © 2014 Author(s).
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-040-511-772-110 tex.type: [object Object]
Keywords: dept.phy

Limits on stellar companions to exoplanet host stars with eccentric planets - Kane, Stephen R; Howell, Steve B; Horch, Elliott P; Feng, Ying; Hinkel, Natalie R; Ciardi, David R; Everett, Mark E; Howard, Andrew W; Wright, Jason T (The Astrophysical Journal, 2014)
Though there are now many hundreds of confirmed exoplanets known, the binarity of exoplanet host stars is not well understood. This is particularly true of host stars that harbor a giant planet in a highly eccentric orbit since these are more likely to have had a dramatic dynamical history that transferred angular momentum to the planet. Here we present observations of four exoplanet host stars that utilize the excellent resolving power of the Differential Speckle Survey Instrument on the Gemini North telescope. Two of the stars are giants and two are dwarfs. Each star is host to a giant planet with an orbital eccentricity >0.5 and whose radial velocity (RV) data contain a trend in the residuals to the Keplerian orbit fit. These observations rule out stellar companions 4-8 mag fainter than the host star at passbands of 692 nm and 880 nm. The resolution and field of view of the instrument result in exclusion radii of 0.″05-1.″4, which excludes stellar companions within several AU of the host star in most cases. We further provide new RVs for the HD 4203 system that confirm that the linear trend previously observed in the residuals is due to an additional planet. These results place dynamical constraints on the source of the planet's eccentricities, place constraints on additional planetary companions, and inform the known distribution of multiplicity amongst exoplanet host stars. © 2014. The American Astronomical Society. All rights reserved..
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-289-457-778-141 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (HD 4203; HD 168443; HD 1690; HD 137759); techniques: Radial velocities; techniques: high angular resolution

High proper motion x-ray binaries from the yale southern proper motion survey - Maccarone, Thomas J.; Girard, Terrence M.; Casetti-Dinescu, Dana I. (Monthly Notices of the Royal Astronomical Society, 2014)
We discuss the results of cross-correlating catalogues of bright X-ray binaries with the Yale Southern Proper Motion Catalog (version 4.0). Several objects already known to have large proper motions from Hipparcos are recovered. Two additional objects are found which show substantial proper motions, both of which are unusual in their X-ray properties. One is IGR J17544-2619, one of the supergiant fast X-ray transients. Assuming the quoted distances in the literature for this source of about 3 kpc are correct, this system has a peculiar velocity of about 275 km s-1-greater than the velocity of a Keplerian orbit at its location of the Galaxy and in line with the expectations formed from suggestions that the supergiant fast X-ray transients should be highly eccentric. We discuss the possibility that these objects may help explain the existence of short gamma-ray bursts outside the central regions of galaxies. The other is the source 2A 1822-371, which is a member of the small class of objects which are low-mass X-ray binaries and long (i.e. >100 ms) X-ray pulsars. This system also shows both an anomalously high X-ray luminosity and a large orbital period derivative for a system with its orbital period, and some possible indications of an eccentric orbit. A coherent picture can be developed by adding in the proper motion information in which this system formed in the Perseus spiral arm of the Galaxy about 3 Myr ago and retains a slightly eccentric orbit which leads to enhanced mass transfer. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00122 tex.type: [object Object]
Keywords: Proper motions; X-rays: binaries; dept.phy; peer-reviewed

An Earth-Sized Planet in the Habitable Zone of a Cool Star. - Quintana, Elisa; Barclay, Thomas; Raymond, Sean; Rowe, Jason; Bolmont, Emeline; Caldwell, Douglas; Howell, Steve; Kane, Stephen; Huber, Daniel; Crepp, Justin; Lissauer, Jack; Ciardi, David; et al. (Science, 2014)
The quest for Earth-like planets is a major focus of current exoplanet research. Although planets that are Earth-sized and smaller have been detected, these planets reside in orbits that are too close to their host star to allow liquid water on their surfaces. We present the detection of Kepler-186f, a 1.11 ± 0.14 Earth-radius planet that is the outermost of five planets, all roughly Earth-sized, that transit a 0.47 ± 0.05 solar-radius star. The intensity and spectrum of the star's radiation place Kepler-186f in the stellar habitable zone, implying that if Kepler-186f has an Earth-like atmosphere and water at its surface, then some of this water is likely to be in liquid form.
189 citations (Crossref) [2023-10-31] Place: Copyright (C) 2014 by the American Association for the Advancement of Science
Keywords: Earth; Earth (Planet); Exobiology; Extraterrestrial Environment; Planets; Stars; Celestial; Water; astrobiology; astronomy; atmosphere; cosmic radiation; dept.phy; habitat use; microclimate; priority journal; review; solar system; surface property; water

Use of the gabor filter for edge detection in the analysis of zinc oxide nanowire images - Scanley, B E; Sadowski, Thomas; Pelligra, Candice; Kreider, M E; Osuji, Chinedum O; Broadbridge, Christine (Microscopy and Microanalysis, 2014)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/150-087-209-672-777 tex.type: [object Object]
Keywords: dept.phy